PEMANFAATAN TEKNOLOGI DALAM PENGEMBANGAN PRODUK TABUNGAN DAN PENGARUHNYA TERHADAP PENINGKATAN NASABAH PADA PT. BANK SYARIAH INDONESIA KC ACEH - Hasnita, Nevi; Fitria, Ana; Maidari, Elisa (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2023)
Bank Syariah Indonesia’s product development entails the application of technology to the creation of product features for Wadiah and Mudharabah savings products, particularly the online account opening method. The purpose of this study was to establish the form of product feature development implemented by Bank Syariah Indonesia KC Aceh, as well as the impact of product development on client acquisition. This research use descriptive qualitative methodology. According to the findings of the study, Bank Syariah Indonesia’s product development may be categorized as modification and growth of product lines and complementary items. The results also indicate that the creation of this product was successful, as evidenced by the increase in the number of new Bank Syariah Indonesia clients who take advantage of the product's new features. In the first year after the launch of this feature in 2020, the number of customers increased by 15,992 or 96.58% compared to the previous year's total of 8,135 clients. This demonstrates that the usage of technology in Bank Syariah Indonesia’s product development has a favorable influence on customer growth.